Maturity model of transdisciplinary knowledge management. Issue 6 (December 2015) - Serna M., Edgar
Highlights The objective is proposing an evolutionary model which accepts knowledge as intensely active and dynamic and evolving in maturity from the early stages of research. But this is possible only if the research team adopt a clear, clean and joint process of disciplinary integration and transdisciplinary integration of the produced and discovered knowledge. In this way, the results of research will have a greater influence on society and they also will be adopted by society.